2007
DOI: 10.1152/ajpheart.00819.2006
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of flow-induced dilation in human adipose arterioles involves hydrogen peroxide during CAD

Abstract: Phillips SA, Hatoum OA, Gutterman DD. The mechanism of flowinduced dilation in human adipose arterioles involves hydrogen peroxide during CAD. Am J Physiol Heart Circ Physiol 292: H93-H100, 2007. First published October 13, 2006; doi:10.1152/ajpheart.00819.2006 is an important physiological stimulus that regulates tissue blood flow and is mediated by endotheliumderived factors that play a role in vascular integrity and the development of atherosclerosis. In coronary artery disease (CAD), conduit artery FID is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
117
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 57 publications
14
117
1
Order By: Relevance
“…By contrast, eNOS expression was decreased under OS in vivo, compared with PS, and in vitro, compared with static controls (figure 3d) [153,155,156]. In agreement with that, isolated arterioles from animals/humans showed NO-dependent dilation under PS or SS; OS did not induce dilation [157,158]. PS (or SS) was found to trigger EC secretion of ATP causing autocrine/paracrine activation of surface purinergic receptors (G q /G 11 protein-coupled P2Y 2 Rs), activation of PLC, generation of IP 3 The pro-inflammatory signalling pathways underlying atherogenesis, including c-Jun N-terminal kinase (JNK)/the family of mitogen-activated protein kinases (MAPKs) and the transcription factors NF-kB and activator protein-1 (AP-1), are redox sensitive [181].…”
supporting
confidence: 83%
“…By contrast, eNOS expression was decreased under OS in vivo, compared with PS, and in vitro, compared with static controls (figure 3d) [153,155,156]. In agreement with that, isolated arterioles from animals/humans showed NO-dependent dilation under PS or SS; OS did not induce dilation [157,158]. PS (or SS) was found to trigger EC secretion of ATP causing autocrine/paracrine activation of surface purinergic receptors (G q /G 11 protein-coupled P2Y 2 Rs), activation of PLC, generation of IP 3 The pro-inflammatory signalling pathways underlying atherogenesis, including c-Jun N-terminal kinase (JNK)/the family of mitogen-activated protein kinases (MAPKs) and the transcription factors NF-kB and activator protein-1 (AP-1), are redox sensitive [181].…”
supporting
confidence: 83%
“…The fluorescence intensity of the central portion of the vessel was obtained in the absence of flow and every 5 min during 10 min of exposure to ANG II (10 Ϫ8 M). Acquired images were analyzed for fluorescence intensity in arbitrary units per minute using NIH Image software, and the rate of superoxide generation was calculated as the change in arbitrary units of fluorescent intensity per minute over the 30-min period normalized to the value in the absence of ANG II (33).…”
Section: Induction Of Akimentioning
confidence: 99%
“…Other data have indicated that flow-induced dilation in visceral fat arterioles is NO dependent in the absence of known coronary artery disease (9). Recent animal data suggested that endothelial nitric oxide synthase (eNOS) knockout mice presented with a phenotype of insulin resistance, hypertension, and dyslipidemia, resembling that observed in human metabolic syndrome, especially under nutritional stress (10,11).…”
Section: Introductionmentioning
confidence: 99%